2018
DOI: 10.1002/jcb.26912
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Beclin‐1 impairs epithelial‐mesenchymal transition of colon cancer cells

Abstract: Activation of autophagy significantly affects cancer cell behaviors, such as proliferation, differentiation, and invasiveness. Epithelial-to-mesenchymal transition (EMT) as an initial step of malignant transformation of cancer cells was linked to the activation of autophagy, but the detailed molecular mechanisms are still unknown. The present study investigates the effects of Beclin-1, a key molecule involved in activation of autophagy, on EMT of colon cancer cells. The normal colon epithelia cell line of CCD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 34 publications
4
30
1
1
Order By: Relevance
“…Although suggested as a tumor suppressor gene, role of Belin-1 in cancer is very complicated and controversial 64 . Recent studies reported that deletion of Beclin-1 expression by RNAi promoted apoptosis in CRC cells 65,66 . Clinical studies have reported that high expression of Beclin-1 in human advanced colorectal cancer tumors is negativity correlated with the survival rate of patients 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Although suggested as a tumor suppressor gene, role of Belin-1 in cancer is very complicated and controversial 64 . Recent studies reported that deletion of Beclin-1 expression by RNAi promoted apoptosis in CRC cells 65,66 . Clinical studies have reported that high expression of Beclin-1 in human advanced colorectal cancer tumors is negativity correlated with the survival rate of patients 67 .…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer cells, autophagy inhibition promotes EMT and alters the metabolic phenotype of cells, and this is dependent on ROS-NF-κB-HIF-1α [38] . In colon cancer cells, Beclin-1 has been shown to be associated with EMT and invasive behaviours; loss of Beclin-1 was able to reverse this phenotype [41] . As described above, autophagy has a dual role: in pancreatic ductal adenocarcinoma cells, TGF-β1 induced autophagy in SMAD4-positive cells and inhibited migration by reducing nuclear translocation of SMAD family member 4 (SMAD4), whereas, in SMAD4-negative cells, migration was increased through mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK) [42] .…”
Section: Emt and Autophagy: A Complex Relationship In Malignancymentioning
confidence: 99%
“…3D). In addition, epithelial-mesenchymal transformation (EMT) plays an important role in the occurrence, development and metastasis of tumors [28,29]. Key transcription factors, including E-cadherin, Ncadherin and vimentin, are extensively involved in the regulation of the EMT process [30].…”
Section: Liquiritin Inhibits Migration and Invasion Of Colorectal Canmentioning
confidence: 99%